Contrast versus non-contrast CT in urinary tract calculi - Faidah, Sofyan; Banjar, Alyaa; Zarbah, Jaber; Alfaer, Sarah; Alshulayyil, Mohammed; Alsalami, Sultan; Alsharif, Maher; Bugis, Bassam; Alshangiti, Ahmad; Alhomidan, Ziad (International Journal Of Community Medicine And Public Health, 2018)
The incidence and prevalence of urinary tract calculi has increased significantly during the past decade. Accurate fast diagnostic modalities were developed to cope with such an increased trend. To date, non-contrast CT scan remains the diagnostic modality of choice for evaluation of patients with urinary tract calculi. However, contrast CT scans are gaining more interest. In this review, both diagnostic modalities were reviewed with the advantages and disadvantages of each. Non-contrast CT scan is a rapid, accurate, less hazardous, less expensive imaging modality that has a high sensitivity in detection of urinary calculi as small as 3 mm. However, it cannot evaluate other probable causes of flank pain. Thus, contrast CT scans can be used in situations where clinical presentation is suspicious and the possibility of other differential diagnoses is considered. Contrast CT scans do not decrease the sensitivity of detecting urinary calculi, and they do have a higher sensitivity in detecting small grades of obstruction as well as evaluating other possible causes of flank pain such as neoplasms, infectious, or inflammatory aetiologies.